"My Life Purpose Is…": Assessment of Youth Purpose in Context. Issue 2 (3rd April 2018) - Linver, Miriam R.; Urban, Jennifer Brown
Abstract : In the introduction to this special issue on youth purpose, the authors discuss the challenges in assessing purpose in adolescents; purpose is a concept that has more often been studied in adults but not in youth. First, theauthors discuss how purpose has been defined in the literature. The authors then situate purpose in the context of a host of related constructs, such as intentional self-regulation, future orientation, goal setting, and identity. Additionally, the authors discuss the importance of accurately measuring youth purpose, as well as in what contexts the assessment of purpose is useful, such as for positive youth development researchers, as well as practitioners and evaluators of youth development programs.